2016
DOI: 10.1002/ppap.201600064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Thermal Atmospheric Pressure Plasma and Sodium Hypochlorite Solution onEnterococcus faecalisBiofilm: An Investigation in Extracted Teeth

Abstract: The aim of this study was to compare the effect of atmospheric pressure plasma (APP) with sodium hypochlorite (NaOCl) or the combination of APP and NaOCl on Enterococcus faecalis biofilm in root canals of extracted human teeth. The disinfection efficiency was determined as the logarithm of the number of colony‐forming units (CFU). Additionally, scanning electron microscopy (SEM) was used to visualize the treatment effect on biofilm. The adjunctive treatment with Plasma + O2 has a small additive, albeit statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
2
9
1
Order By: Relevance
“…SEM showed no colonization in the dentinal tubules after using plasma/O 2 . Similar effects were shown by others and our working group [18,19]. Unlike our CFU analysis, scanning electron micrographs indicate an additive effect of the combined therapies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…SEM showed no colonization in the dentinal tubules after using plasma/O 2 . Similar effects were shown by others and our working group [18,19]. Unlike our CFU analysis, scanning electron micrographs indicate an additive effect of the combined therapies.…”
Section: Discussionsupporting
confidence: 90%
“…Antifungal activity of plasma/O 2 was time‐dependent. Earlier studies could demonstrate similar observations [19, 26]. Previous studies indicated oxidation processes caused by reactive oxygen species to be responsible for the disinfecting effect of plasma [14].…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…CAPs are known to effectively inactivate bacteria and fungi (independent of their resistance profiles towards conventional antimicrobials as well as on different surfaces and in biofilms), spores and viruses [17, 18]. Furthermore, it could be shown that CAP doses can be found where pathogens can be inactivated without mammalian tissues being harmed or without changing the characteristics of the respective materials that bacteria are attached to [19, 20]. Due to these results and, moreover, as CAP operate at low temperatures (5–10°C above room temperature only), various applications in hygiene ( e .…”
Section: Introductionmentioning
confidence: 99%